Integrating smart technologies in ecotourism opportunities development - R. M. Sahahiri (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Ecotourism is recognised as a sustainable tourism paradigm that harmonises environmental preservation with economic and cultural advantages. This study examines the integration of advanced technologies, particularly Geographic Information Systems (GIS), remote sensing, and mobile applications, in evaluating and developing Alula's ecotourism opportunities. It employs a mixed-method approach to examine Alula's viability for ecotourism, including essential environmental, topographical, and infrastructural elements, as well as evaluating tourist preferences and stakeholder perspectives on technology adoption. The GIS and remote sensing research determined that Alula's mild temperature (22.5°C), low population density (2.44 individuals/km2), and slope changes (0–27%) render it an appropriate location for ecotourism. Moreover, the prominent visibility of picturesque locations, closeness to historical sites (0–15 km), and accessibility through road infrastructure augment its tourism potential. Water shortage (21 mm annual rainfall) and habitat fragmentation persist as challenges necessitating sustainable management techniques. The mobile application survey indicated a significant preference for real-time navigation, cultural heritage information, and sustainability education functionalities. Stakeholder interviews highlighted the significance of integrating smart technology to enhance visitor management, resource conservation, and tourist planning. This study combines GIS-based suitability analysis with mobile technology uptake to develop a comprehensive framework for smart ecotourism planning in ecotourism destinations. The findings emphasise the need for GIS and remote sensing for land-use optimisation, mobile apps for visitor interaction, and sustainable infrastructure policies. Tourism planners, environmentalists, and lawmakers might learn from the proposed paradigm on sustainable ecotourism and smart tourism in heritage-rich places.